Study of the Multiplication and Distribution Programme for Improved Seed - Planning Commission (Planning Commission, 1961)
The economic importance of pure seed of improved variety is one of the most well-recognised facts about agriculture. Almost every cultivator knows the potentiality of improved seed for raising the level of return from a crop. In fact, no other method of agricultural improvement meets with as ready a response and adoption from the farmers as the use of improved seed. It is to him one of the easier and relatively less costly of the improved practices. for this and other reasons, administrators, planners, extension workers and agricultural scientists have long been interested in this field. Official efforts for seed improvement and extension in India date back, at least, to the early years of this century. the progress in evolving improved seeds and extending their use has been reviewed off and on over this period,
Programme Evaluation Organisation Planning Commission Government of India